West Nile Virus in Brazil - Costa, ?rica Azevedo (MDPI, 2021)
Background: West Nile virus (WNV) was first sequenced in Brazil in 2019, when it was isolated from a horse in the Esp?rito Santo state. Despite multiple studies reporting serological evidence suggestive of past circulation since 2004, WNV remains a low priority for surveillance and public health, such that much is still unknown about its genomic diversity, evolution, and transmission in the country. Methods: A combination of diagnostic assays, nanopore sequencing, phylogenetic inference, and epidemiological modeling are here used to provide a holistic overview of what is known about WNV in Brazil. Results: We report new genetic evidence of WNV circulation in southern (Minas Gerais, S?o Paulo) and northeastern (Piau?) states isolated from equine red blood cells. A novel, climate-informed theoretical perspective of the potential transmission of WNV across the country highlights the state of Piau? as particularly relevant for WNV epidemiology in Brazil, although it does not reject possible circulation in other states. Conclusion: Our output demonstrates the scarceness of existing data, and that although there is sufficient evidence for the circulation and persistence of the virus, much is still unknown on its local evolution, epidemiology, and activity. We advocate for a shift to active surveillance, to ensure adequate preparedness for future epidemics with spill-over potential to humans.